Rose Bengal and Mercaptoethanol Tests for the Diagnosis of Brucella abortus Biotype-1 Infection in Sprague-Dawley Rats (Biological Sciences - PJSIR, 2005)
Rose Bengal test (RBT) and mercaptoethanol test (MET) were conducted for the diagnosis of Brucella abortus biotype-1 infection. For this purpose, female Sprague-Dawley (S-D) rats were subcutaneously infected at the dose rate of 1.0×109 colony forming unit suspension of B. abortus in physiological saline. The S-D rats were monitored at regular intervals using serological and bacteriological methods. The reciprocal antibody titer after the first week was 1: 800 with RBT, whereas it was 1: 400 with MET. The reciprocal antibody titer of 1: 25 through RBT and 1:100 through MET, respectively, were noted in infected rats of 24 weeks post-infection. Bacteremia was detected untill 24 weeks post-infection. RBT, using B. abortus strain S1119-3 whole cell antigen, appears to be a potential candidate, as a useful diagnostic method, for brucellosis detection in rats.